Effect of Bacillus subtilis Strains on Intestinal Barrier Function and Inflammatory Response - Rhayat, Lamya; Maresca, Marc; Nicoletti, Cendrine; Perrier, Josette; Brinch, Karoline Sidelmann; Christian, Sonja; Devillard, Estelle; Eckhardt, Erik (Frontiers in Immunology, 2019)
Strong tight junctions and curtailed inflammatory responses under stressful conditions are key for optimal digestive health. Bacillus-based probiotics are increasingly being used to maintain broilers’ health, but their mode of action is often not well defined. In the present study we used Caco-2 cells as a model for intestinal epithelia and assessed the effect of three Bacillus-based probiotics on intestinal barrier function and intestinal inflammation. Experimental results showed that one of the three tested strains significantly reinforced intestinal barrier integrity under basal conditions, whereas the others had no or detrimental effects. When Caco-2 cells were pre-treated with Bacillus subtilis strains, the subsequent IL-8 release to various pro-inflammatory signals (IL-1β, deoxynivalenol, or flagellin) was blunted compared to cells that had not been pretreated, but to a different extent depending on the strain of Bacillus used. One strain, Bs 29784, was able to significantly decrease IL-8 production in all stressed conditions tested. Mechanistically, Bs 29784 appeared to limit nuclear translocation of NF-κB during IL-1β exposure by preventing IκB degradation. The effects of Bs 29784 were observed independently with supernatant and cells but in a lesser extent than with the combination, indicating that they can thus likely be attributed to both secreted metabolites and cell-associated compounds. Moreover, under inflammatory conditions, Bs 29784 significantly reduced the upregulation of iNOS protein levels further underlining its intestinal anti-inflammatory potential. Our data show that Bacillus-based probiotics may indeed improve digestive health by strengthening intestinal barrier and limiting inflammatory responses and that these properties are strain-dependent.